Effect of dietary supplementation of rice bran crude lecithin on nutrient metabolism, methanogenesis and metabolic profile of crossbred calves - DHARMESH TEWARI; V B CHATURVEDI; L C CHAUDHARY; A K VERMA; S K CHAUDHARY (Indian Journal of Animal Sciences, 2022)
The present study was conducted to evaluate the effect of rice bran crude lecithin (RBCL) on nutrient digestion and balance, performance, methanogenesis and blood profile in crossbred calves. Crossbred calves (18) were randomly divided into three groups; RBCL-0, RBCL-8 and RBCL-12 and fed wheat straw based diet with concentrate mixture containing 0, 8 and 12% RBCL respectively. The dry matter, organic matter and crude protein intake were comparable but tended to decrease with the RBCL levels. The digestibility of dry matter, organic matter, total carbohydrate and gross energy decreased while crude protein and ether extract digestibility increased with RBCL levels. Fibre fractions (NDF and ADF) digestibility was significantly lower in RBCL supplemented groups in comparison to control group. The body weight gain and average daily gain decreased with increasing level of RBCL. The per cent of nitrogen and calcium retention decreased, while phosphorus retention was significantly lower with inclusion levels of RBCL. Methane production (L/d, L/kgW0.75) was significantly lower in RBCL-12 followed by RBCL-8 as compared to RBCL-0 group. The cholesterol and blood urea concentration was significantly higher in RBCL-12 group as compared to control group. It can be concluded that RBCL is helpful in methane mitigation for cleaner production and can be a cheap source of energy in place of corn for ruminants but at present levels (8 and 12%) the average daily gain depression was seen. Further studies in large number of livestock are warranted to explore the potential of RBCL in the ruminant ration.